Post Solution Posing Based on Qiraah Learning Model for Developing Critical Thinking Process - Puti Zulharby; Fatwa Arifah; Ahmad Marzuq; Mohamad Sarip; Waldi Awali Syah (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This research aimed to provide solutions to Qiraah teachers, in order to train and develop students' thinking abilities through a post-solution position-based learning model. The development of the learning model is based on the Qiraah learning constraints and problems faced by lecturers and students, which are obtained from needs analysis. The post-solution posing model applies six phases in learning activities, namely establishing set, comprehension, social interaction, explain, feedback, and extended practice. This research used research and development method. Data are collected through questionnaire, interview, document, and test conducted in the Arabic Language Education Study Program involving 45 students. The effectiveness of the six phases of the post-solution posing model which has been tested on learning through Qiraah using the one-group pretest-posttest technique, produces a significance value (2-tailed) of 0.000 (p < 0.05). This shows a significant increase in scores, so that the post-solution position learning model in the Qiraah course is considered effective for training the development of thinking skills in students.